Peran Balai Taman Nasional Wasur Dalam Meningkatkan Pendapatan Masyarakat lokal Kampung Wasur - Paul Adryani Moento; Nikolaus Unawekla (Musamus Journal of Public Administration, 2019)
The welfare level of the population in Wasur Park village is still very low and most still hang its life by taking the result of the forest. This study aims to analyze the role of Wasur Park National Park in increasing local people's income. The method by which researchers use a qualitative approach, while the data collection techniques consist of library studies and field studies through observation, interviews. The process of data analysis includes data reduction, data presentation, and the conclusion of the empowerment of the National Park Wasur Park Hall is counseling to the local community in the framework of the Empowerment Program of local Kampung Wasur Park. In the empowerment, Wasur Park National Park is coordinating with local governments to see the development of local community data. The real evidence of Wasur Park National Park through empowerment is the establishment of a rural forestry Counseling Center (SPKP). The establishment of a rural forestry Counseling Center (SPKP) in Wasur Village, implemented after the implementation of education and training of village studies in participatory. Furthermore, Wasur Park National Park Hall conducts construction. The construction is a construction of small industry of eucalyptus oil refining, the manufacture of salted fish, medicinal plants, and the cultivation of commercial crops. Then the community in providing coaching through socialization by providing science about preserving the forest and protection and safeguarding the potential of Wasur National Park area. Then Wasur Park National Park Hall conducts supervision. Supervision conducted by the National Park Hall Wasur Park is monitoring against the hunting of many protected animals located in Wasur Park National Park area. In the Garden Hall program, Wasur Park is monitoring and evaluation of habitat and population. The Wasur Park National Park Hall conducts a regular patrol, preventing wild hunters from Wasur Park National Park. Then patrol is also done to prevent forest fires.